Computer Network Security and Privacy: A Review - Amruta Kalambe; Smruti Malik (Journal of Electronic Design Engineering, 2022)
The widespread use of laptop community programs has come a high level of concern for their security. Complex factors influence community protection. A challenging scientific endeavor, network security. The goal of this paper is to raise security awareness among computer network users and help them understand effective community safety technology. It does this by combining practical work experience with the risk of community safety, safety technology, and community a few suggestions and measures for the device design principle.